Quick Start - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
LogiQL is a powerful language containing many features to be described in the upcoming chapters. The text includes numerous embedded examples and exercises that you are encouraged to try out for yourself. There are several ways to actually run your programs including a Web-based interpreter, a sophisticated middleware interface, and the one we choose to use in this book, a command-line interface, called lb. The lb command and its subcommands are described in Appendix A, but in this section, we will take you through a short example so you can quickly get started using LogiQL. The example covers how you use lb and LogiQL to declare predicates and constraints, define rules, enter data, and query the results. In particular, it computes for each member of the British monarchy those other monarchs who were his or her ancestors.